Factors Related to the Low Use of Intraceptive Devices (IUD) in Women Couple of Reproductive Age at Public Health Center Tiga Balata, Simalungun Regency - Riada Mareny; Mei Linawati Siahaan; Arfyah Sagita Yunanda (PT Inovasi Pratama Internasional, 2022)
The Family Planning Program (KB) is a national program that improves the health status and welfare of women, children and families in particular, and the nation in general. The use of the IUD method in Indonesia is able to significantly reduce the Total Fertiliry Rate (TFR). The IUD is an effective contraceptive device but can cause interference with the reproductive organs due to its presence in the uterus where the IUD is a foreign body for the uterus so that it causes many side effects for the acceptor, for example resulting in increased volume and length of menstruation (metroragia) caused by mechanical factors in the uterus. endometriosis due to a mismatch between the size of the IUD and the uterine cavity and possibly due to intra-uterine or ectopic pregnancies. The purpose of this study was to determine the factors associated with low use of intrauterine contraceptive devices (IUD) in women of childbearing age couples at Tiga Balata Health Center. The results of the study based on the results of the Chi-Sguare statistical test showed that there was a relationship between age and IUD use p value = 0.001 ≤ α (0.05), there was a relationship between education and IUD use p value = 0.006 ≤ α (0.05,) there was a relationship between knowledge and IUD use p value = 0.019≤ α (0.05), there is a relationship between the number of children and IUD use p value=0.004 ≤α(0.05), there is a relationship between the availability of equipment and IUD use p value=0.000 ≤ α (0.05 ), there is a relationship between the support of health workers and IUD use p value = 0.001≤ α (0.05), there is a relationship between family support and IUD use p value = 0.008 ≤ α (0.05).